Effect of Laser Cutting Methods on Hole Deviation and Surface Integrity - Rijab, Mustafa Ahmed; Mahdi, Hamid Salih (Al-Khwarizmi Engineering Journal, 2012)
In the present work usedNd:YAG laser systems of different output characteristic were employed to study the drilling process of material used in scientific and industrial fields. This material include Manganese hard steel. Our study went into the affecting parameters in drilling of Manganese hard steel by laser. Drilling process is achieved through material absorption of part of the incident laser beam. It is the resultant of interfering both, laser beam and material properties and the focusing conditions of the beam. The results as shown that the increase in the laser pulse energy over the used level has raised the hole diameter, depth and increased the hole taper. In addition to that a hole taper was affected by the laser energy, the focusing position and focal length of the lens used.